The effects of second screen use on sponsor brand awareness: a dual coding theory perspective - Jensen, Jonathan A; Walsh, Patrick; Cobbs, Joe; Turner, Brian A (The Journal of consumer marketing, 2015)
Purpose – The purpose of this paper is to investigate how simultaneous use of devices such as personal computers, tablets and smartphones impacts the sponsors that receive brand integration during the broadcasts. Advances in technology now allow fans to consume broadcasts of televised events almost anywhere via personal computers, tablets and smartphones. These devices are also frequently utilized as “second screens” to communicate with fellow consumers on social media, access additional content or otherwise multitask during televised consumption. Design/methodology/approach – An initial study served to test the applicability of the theoretical framework of a dual coding theory in this new context, followed by a 3 × 2 between-subjects design utilized to advance understanding of the influence of second screens on brand awareness of the sponsors of televised events. Findings – Results demonstrated that both brand recognition and recall were reduced by second screen activity across nearly all audio or visual consumption experiences. Further, while second screen use in an audiovisual setting did not interfere with consumers’ ability to recognize brands, indicating they were able to multitask and were not distracted, it inhibited their ability to recall brands from memory. This result provides evidence that second screen use may interfere with elaborative rehearsal and reduce cognitive capacity. Practical implications – Given that marketers are investing more resources than ever to achieve brand integration during televised events, these findings suggest that brands face challenges in achieving a requisite return on their investments. Originality/value – This study represents the first empirical investigation of the impact of consumers’ use of second screens in the academic literature, and has important implications for the sponsors of televised events.